Predicting outcomes of breast-conserving surgery in patients with breast cancer using the modified 5-Item frailty index: a retrospective cohort study - Knoedler, Samuel; Jiang, Jun; Moog, Philipp; Wirtz, Julius M.; Schaschinger, Thomas; Mayer, Horacio; Machens, Hans-Guenther; Könneker, Sören; Hundeshagen, Gabriel; Kim, Bong-Sung; Orgill, Dennis P.; Panayi, Adriana C. (Annals of surgical oncology, 2025)
Background. Breast cancer is the most common malignancy among women worldwide, with breast-conserving surgery (BCS) being a key treatment. The modified 5-item frailty index (mFI-5), a well-validated tool for assessing frailty, has shown predictive utility in other surgical contexts but remains under-explored in BCS. Patients and Methods. Using the American College of Surgeons National Surgical Quality Improvement Program database (2008–2021), we identified adult female patients with breast cancer who underwent BCS. Frailty was assessed using the mFI-5 and scored from 0 to 5, with higher scores indicating greater frailty. Multivariable logistic regression was employed to evaluate associations between mFI-5 scores and postoperative outcomes. Results. A total of 96,586 patients were included. Higher mFI-5 scores were significantly associated with older age, higher body mass index (BMI), and increased ASA scores. Multivariate analysis showed greater frailty was linked to higher risks of any (mFI = 1: OR 1.06; mFI = 2: OR 1.26; mFI ≥ 3: OR 2.45), surgical (mFI = 1: OR 1.18; mFI = 2: OR 1.65; mFI ≥ 3: OR 3.17), and medical complications (mFI = 1: OR 1.72; mFI = 2: OR 2.56; mFI ≥ 3: OR 6.05). Similarly, frail patients had significantly higher odds of mortality (mFI = 1: OR 2.27; mFI = 2: OR 4.3; mFI ≥ 3: OR 11.05) and unplanned readmission (mFI = 1: OR 1.38; mFI = 2: OR 2.25; mFI ≥ 3: OR 6.05). Reoperation risk decreased with higher mFI-5 scores (mFI = 1: OR 0.92; mFI = 2: OR 0.73; mFI ≥ 3: OR 0.92). Conclusions. The mFI-5 is strongly associated with postoperative outcomes after BCS and serves as a valuable tool for risk stratification. Our findings reinforce its role as a critical preoperative index to identify high-risk patients and guide surgical planning.
Gesehen am 04.11.2025